High referral accuracy for oral cancers and oral potentially malignant disorders using telemedicine. (11th May 2021) - Haron, Nabihah; Rajendran, Senthilmani; Kallarakkal, Thomas George; Zain, Rosnah Binti; Ramanathan, Anand; Abraham, Mannil Thomas; Lau, Shin Hin; Cheng, Lai Choo; Chong, Sherrie Mei Yee; Mohamed Azahar, Farah Aliya; Mohamad Zaini, Zuraiza; Chan, Siew Wui; et al.
Abstract: Objective: To evaluate the accuracy of MeMoSA®, a mobile phone application to review images of oral lesions in identifying oral cancers and oral potentially malignant disorders requiring referral. Subjects and Methods: A prospective study of 355 participants, including 280 with oral lesions/variants was conducted. Adults aged ≥18 treated at tertiary referral centres were included. Images of the oral cavity were taken using MeMoSA®. The identification of the presence of lesion/variant and referral decision made using MeMoSA® were compared to clinical oral examination, using kappa statistics for intra‐rater agreement. Sensitivity, specificity, concordance and F1 score were computed. Images were reviewed by an off‐site specialist and inter‐rater agreement was evaluated. Images from sequential clinical visits were compared to evaluate observable changes in the lesions. Results: Kappa values comparing MeMoSA® with clinical oral examination in detecting a lesion and referral decision was 0.604 and 0.892, respectively. Sensitivity and specificity for referral decision were 94.0% and 95.5%. Concordance and F1 score were 94.9% and 93.3%, respectively. Inter‐rater agreement for a referral decision was 0.825. Progression or regression of lesions were systematically documented using MeMoSA®. Conclusion: Referral decisions made through MeMoSA® is highly comparable to clinical examination demonstrating it is a reliable telemedicine tool to facilitate the identification of high‐risk lesions for early management.